2018
DOI: 10.1093/jscr/rjx264
|View full text |Cite
|
Sign up to set email alerts
|

A novel safe approach to laparoscopic colorectal cancer resection in patients with ventriculoperitoneal shunt: report of two cases and literature review

Abstract: There is ongoing challenges regarding the safety of performing laparoscopic surgery with the presence of ventriculoperitoneal (VP) shunts, especially in patients treated for cancer disease. To date, only one case has been reported in the English literature. Herein, we report an additional two cases of patients with previous insertion of a VP shunt, diagnosed with colon cancer. Both our patients underwent successful laparoscopic colectomies, without clamping or removal of the VP shunt, with no reported perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Neale et al reported that if the pneumoperitoneum pressure did not exceed 80 mmHg, no cerebrospinal fluid reflux occurs in the VP shunt [ 9 ]. Therefore, laparoscopic surgery with pneumoperitoneum pressure of 8–10 mmHg generally does not cause reflux in the VP shunt, and there have been many reports of laparoscopic procedures performed with the VP shunt that ended without trouble [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neale et al reported that if the pneumoperitoneum pressure did not exceed 80 mmHg, no cerebrospinal fluid reflux occurs in the VP shunt [ 9 ]. Therefore, laparoscopic surgery with pneumoperitoneum pressure of 8–10 mmHg generally does not cause reflux in the VP shunt, and there have been many reports of laparoscopic procedures performed with the VP shunt that ended without trouble [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a topic of concern that due to CO 2 insufflation, the pneumoperitoneum may induce CSF shunt-related spread of cancer cells such as subcutaneous seeding or retrograde metastasis [ 3 , 4 ]. Recently, long-term outcomes of large, randomized trials comparing open and laparoscopic surgeries for colorectal cancer demonstrated the noninferiority of laparoscopic surgery for treating T4 tumors and an actual incidence of port-site metastasis of approximately 1%, which is not significantly different from wound recurrence rate after open colorectal surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the demand for minimally invasive surgeries increases, most abdominal surgeries are now being performed laparoscopically. Although there are several reports on laparoscopic surgery for patients with CSF shunt, laparoscopic colectomy for patients with CSF shunt has been rarely reported [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%